1996
DOI: 10.1089/neu.1996.13.41
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Environmental Complexity Promotes Recovery of Cognitive Function after Traumatic Brain Injury

Abstract: This study was designed to determine whether exposure to a complex environment after traumatic brain injury (TBI) would promote the recovery of cognitive function. Rats were injured at a moderate level of fluid percussion injury (2.1 atm) or were prepared for injury but were not injured (sham injury). Immediately after the injury or sham injury, the injured/complex (n = 8) and the sham/complex (n = 7) groups were placed into a complex environment. The complex environment was a 89 x 89-cm enclosure with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
116
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 49 publications
7
116
0
1
Order By: Relevance
“…There was also a significant main effect of group [F(2,27) = 18.93, p < 0.001), but not a group by trial interaction. Post hoc tests indicated that the FP+EE group and the sham group performed significantly better than the FP group (p < 0.001), which is in agreement with previous studies [28,35,59]. Swim speeds did not vary between groups.…”
Section: One-hour Of Daily Environmental Enrichment Attenuates Cognitsupporting
confidence: 90%
See 2 more Smart Citations
“…There was also a significant main effect of group [F(2,27) = 18.93, p < 0.001), but not a group by trial interaction. Post hoc tests indicated that the FP+EE group and the sham group performed significantly better than the FP group (p < 0.001), which is in agreement with previous studies [28,35,59]. Swim speeds did not vary between groups.…”
Section: One-hour Of Daily Environmental Enrichment Attenuates Cognitsupporting
confidence: 90%
“…To determine if the experimental manipulations that we used in this study for the EE (1 h/d X 3 weeks) produced improvements in behavior following FP injury similar to those reported in previous studies (24 h/d X 2 weeks) [28,35,59], we added additional animals to the study and evaluated spatial learning and memory in a MWM across groups. In general, performance improved over trial blocks [F(3,36) = 32.75, p <0.001] for all groups (Fig.…”
Section: One-hour Of Daily Environmental Enrichment Attenuates Cognitmentioning
confidence: 99%
See 1 more Smart Citation
“…The workshop leaders focused exclusively on the potential for combinatorial pharmacological agents to promote recovery. While this is a commendable start, there is certainly real potential and value in including non-invasive therapies, such as environmental enrichment (EE) or exercise (Gomez-Pinilla et al, 2011;Griesbach et al, 2009;Hamm et al, 1996;Hicks et al, 2002;Hoffman et al, 2008;Kline et al, 2007Kline et al, ,2010Matter et al, 2011;Passineau et al, 2001;de Witt et al, 2011), in combinational therapy paradigms for promoting recovery and perhaps augmenting the pharmacological effects, particularly in rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm has consistently shown improvements in behavioral and histological outcome after brain trauma and can therefore be considered a reasonable approach to preclinical rehabilitation. Importantly, the benefits conferred by EE span clinically-relevant models of experimental TBI, such as controlled cortical impact (CCI; Chen et al, 2005;de Witt et al, 2011;Hoffman et al, 2008;Kline et al, 2007Kline et al, ,2010Matter et al, 2011;Sozda et al, 2010) and fluid percussion (Hamm et al, 1996;Hicks et al, 2002;Gaulke et al, 2005;Giza et al, 2005;Maegele et al, 2005;Passineau et al, 2001). The second therapy in this combined treatment approach is the systemic administration of the serotonin 1A (5-HT 1A )-receptor agonist buspirone.…”
Section: Introductionmentioning
confidence: 99%